Hepatitis C, Illicit Drug Use and Public Health: Does Canada Really Have a Viable Plan? - Fischer, Benedikt (Can J Public Health, 2006)
Some 300,000 individuals are infected with the hepatitis C virus (HCV) in Canada. HCV infection is associated with major morbidity, mortality and health care costs; these indicators are projected to rise over the next decade. The vast majority of prevalent and incident HCV infections in Canada are illicit drug use-related; thus, the HCV disease burden can only be addressed through interventions targeting this primary risk factor. Both preventive (e.g., needle exchange, methadone treatment) and therapeutic (e.g., the accessibility of HCV treatment for illicit drug users) interventions aimed at HCV in illicit drug users have been broadly expanded in Canada in recent years. However, evidence suggests that existing preventive measures only offer limited effectiveness in reducing HCV risk exposure. Also, due to restricted resources, treatment for HCV currently only reaches an extremely small proportion (i.e., <5%) of HCV-infected drug users. Thus, on the basis of current HCV incidence as well as given interventions and their impact, Canada is not achieving a net reduction in the prevalence of HCV-related to illicit drug use. In order to reduce the HCV disease burden, Canada needs to reconsider the scope, delivery and resourcing of both preventive and treatment interventions targeting the primary risk population of illicit drug users.